Design and Implementation of High Efficient Single Phase Transformer Less Inverter for Grid Connected Solar Photovol-taic Energy System - Babu, Attuluri R.Vijay; Suresh, K.; Krishna, Pillutla Murali; Hussain, Shaik Ashfaq (International Journal of Engineering and Technology, 2018)
Solar energy is the most available energy among all the renewable energies, and the available range is almost 86000 TW. The global overall demand is 15TW, so only three hours production of electrical energy from solar is enough to compensate the power demand for a complete year.Clean and green environments are very much help for living things, non-renewable energy productions creates environmental pollution. Stand-alone system with renewable energy might be facing power failure and also effective utilizations also not possible. Excess power should be export to grid and whenever the power shortage which is compensates by import power from grid, and then only effective utilization is possible. This paper deals with the investigations on transformer less inverter topologies and control strategies for grid connected PV system. The proposed work has high efficient single phase transformer less inverter which is controlled by PIC 16F877. This arrangement has an advantage of reliability and high level of efficiency.